2020
DOI: 10.1111/bcp.14459
|View full text |Cite
|
Sign up to set email alerts
|

Serious adverse events with tocilizumab: Pharmacovigilance as an aid to prioritize monitoring in COVID‐19

Abstract: Given its approval for the treatment of cytokine release syndrome, tocilizumab is under investigation in severe coronavirus disease-2019. To characterize serious adverse events (AEs) with tocilizumab, we queried the worldwide FDA Adverse Event Reporting System and performed disproportionality analysis, selecting only designated medical events (DMEs) where tocilizumab was reported as suspect, with a focus on hepatic reactions. The reporting odds ratios (RORs) were calculated, deemed significant by a lower limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 23 publications
0
38
0
4
Order By: Relevance
“…10 In the absence of a proven effective antiviral therapy, and because of its approval in cytokine release syndrome, tocilizumab has been considered a promising drug for the treatment of severe COVID-19 infections. 17 Clinical studies have shown very good effects of tocilizumab on clinical and biochemical parameters in patients with COVID-19. For this reason, tocilizumab, a humanized monoclonal antibody against the IL-6 receptor (IL-6R), has been recommended in severe COVID-19 disease by the National Health Commission of China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In the absence of a proven effective antiviral therapy, and because of its approval in cytokine release syndrome, tocilizumab has been considered a promising drug for the treatment of severe COVID-19 infections. 17 Clinical studies have shown very good effects of tocilizumab on clinical and biochemical parameters in patients with COVID-19. For this reason, tocilizumab, a humanized monoclonal antibody against the IL-6 receptor (IL-6R), has been recommended in severe COVID-19 disease by the National Health Commission of China.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a proven effective antiviral therapy, and because of its approval in cytokine release syndrome, tocilizumab has been considered a promising drug for the treatment of severe COVID-19 infections. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Tocilizumab, a humanized monoclonal antibody against the interleukin-6 receptor, is also known to cause severe liver injury. 23 A retrospective, observational cohort study reported a decreased need for invasive mechanical ventilation and a lower risk of death in patients with severe pneumonia. In this study, when compared with the standard care group, the tocilizumab group had a significantly higher elevation of ALT.…”
Section: Mechanism Of Hepatic Injury From Sars-cov-2 Virusmentioning
confidence: 99%
“…Besides, unlike TCs, tocilizumab is an expensive drug that also needs close monitoring during its parenteral administration since it may cause serious anaphylactic reactions, liver injury, and secondary bacterial infections (Stone et al, 2020). On the other hand, TCs are cheap, safe, and effective orally, not needing close monitoring and neither increasing the risk of bacterial coinfection; therefore, TCs are more effective than tocilizumab in the management of COVID-19 (Gatti et al, 2020).…”
Section: Anti-inflammatory Effects Of Tetracyclines In Covid-19mentioning
confidence: 99%